Cellular Imaging: a Key Phenotypic Screening Strategy for Predictive Toxicology - JINGHAI JAMES XU (Frontiers Media S.A., 2015)
Incorporating phenotypic screening as a key strategy will enhances confidence in the predictivity and translatability of drug discovery efforts. Cellular imaging serves as the a phenotypic anchor to identify important toxicologic pathology that encompasses an array of underlying mechanisms, thus provides an effective means to reduce drug development failures due to insufficient safety. This mini-review highlights the latest advances in hepatotoxicity, cardiotoxicity, and genetic toxicity tests that utilized cellular imaging as a screening strategy, and recommends path forward for further improvement.